Association between the severity of gingival inflammation and microbial findings in children - Tankova, Hristina (Frontiers in Dental Medicine, 2025)
IntroductionThe oral cavity is home to hundreds of distinct microbial species, and specific periodontal pathogens are isolated from different ecological niches. Present study aimed to investigate the relationship between the severity of gingival inflammation and the presence of subgingival microorganisms in children with dental biofilm induced gingivitis.Material and MethodsThe study included 30 children aged 12–14 years, divided into two groups based on the extent of gingival inflammation: Group I—16 children with BOP up to 30%; Group II—14 children with BOP over 30%. All children were interviewed to assess oral hygiene habits. Clinical examination was performed using an electronic periodontal probe, and the following were recorded: oral hygiene status (FMPS) and gingival status through BOP and SBI. For quantitative assessment of subgingival periodontopathogens, a genetic method - PCR—Real Time was used, and the following microorganisms were examined: Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, Prevotella intermedia, Peptostreptococcus micros, Fusobacterim nucleatum, Eubacterium nodatum, Capnocytophaga gingivalis. The critical significance level for testing the null hypothesis was set at α = 0.05, corresponding to a 95% confidence level.ResultsThe majority of children showed improper oral hygiene habits. Children with generalized gingival inflammation had significantly higher plaque accumulation index values compared to those with localized inflammation. In children with generalized gingival inflammation, the quantities of all isolated periodontopathogens were higher compared to those with localized inflammation, which was also confirmed regarding the overall microbial load. A. actinomycetemcomitans was not isolated in children with localized gingival inflammation, while T. denticola was isolated in significantly lower quantities compared to generalized inflammation. P. intermedia and P. micros were isolated in significantly higher quantities in more severe gingival inflammation. In children with localized gingival inflammation, combinations of an average of 2 microorganisms were found in microbial complexes, while in children with generalized inflammation, microorganisms were twice as many and in more complex combinations.ConclusionThe microbial diversity within the subgingival biofilm significantly increases with disease severity, providing further evidence for the critical role of microbial ecology in the pathogenesis of gingival inflammation in children.